2019
DOI: 10.5114/ada.2018.77056
|View full text |Cite
|
Sign up to set email alerts
|

The role of Staphylococcus aureus in atopic dermatitis: microbiological and immunological implications

Abstract: IntroductionAtopic dermatitis (AD) is an inflammatory disease characterised by chronic and recurrent course. Its predominant symptom is skin pruritus. Therefore, many AD patients have recurrent skin infections and are susceptible to the colonisation of apparently healthy skin and nasal vestibule by Staphylococcus aureus (S. aureus). Some S. aureus strains are capable of producing exotoxins.AimTo assess the relation between the total IgE (tIgE) and asIgE targeted against SEA (SEA-sIgE) and SEB (SEB-sIgE), as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Beyond its role in maintaining the homeostasis of the skin’s microbiome, C. acnes may become “pathogenic” for the skin. It has long been implicated in the pathogenesis of acne 29 . An unbalancing in the bacterial population, including C. acnes and S. aureus has been also recently reported in other skin conditions such as seborrheic dermatitis 30 , psoriasis, and rosacea 31 , and alopecia 32 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Beyond its role in maintaining the homeostasis of the skin’s microbiome, C. acnes may become “pathogenic” for the skin. It has long been implicated in the pathogenesis of acne 29 . An unbalancing in the bacterial population, including C. acnes and S. aureus has been also recently reported in other skin conditions such as seborrheic dermatitis 30 , psoriasis, and rosacea 31 , and alopecia 32 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the concentration of IgE increased further when the mouse backs were painted with S. aureus SA-1 ( Figure 5 b). It has been reported that various toxins produced by S. aureus induce IgE expression [ 15 , 16 ]. Treatment with phage SaGU1 significantly decreased the plasma levels of IgE by 53% in S. aureus -painted mice.…”
Section: Resultsmentioning
confidence: 99%
“…aureus was related to higher total IgE serum levels, which correlated with disease course. Additionally, significantly increased staphylococcal enterotoxin A‐specific IgE and staphylococcal enterotoxin B‐specific IgE concentrations were observed in AD patients with higher total IgE serum concentrations 80,81 …”
Section: Cutaneous Infections In the Pathogenesis Of Admentioning
confidence: 99%
“…Additionally, significantly increased staphylococcal enterotoxin A-specific IgE and staphylococcal enterotoxin B-specific IgE concentrations were observed in AD patients with higher total IgE serum concentrations. 80,81 Decreased expression of antimicrobial peptides (AMPs), such as human β-defensins (hBDs), cathelicidin LL-37 and dermcidin, has been documented in AD lesional skin compared with psoriasis, a skin condition also characterized by an impaired skin barrier. 82,83 The observation that patients with psoriasis do not show frequent staphylococcal infections compared with AD patients is in part explained by high production of AMPs in psoriasis and low production of these molecules in AD.…”
Section: The Role Of Bacteriamentioning
confidence: 99%